2021
DOI: 10.1155/2021/6664058
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Two Different Modes of Task Practice during Lower Limb Constraint-Induced Movement Therapy in People with Stroke: A Randomized Clinical Trial

Abstract: Background. Constraint-induced movement therapy (CIMT) is used for the rehabilitation of motor function after stroke. Objectives. The aim of this study was to compare the effects of lower limb CIMT that uses number of repetition of tasks with the one that uses number of hours of practice. Method. The study was a randomized clinical trial approved by the Ethics Committee of Kano State Ministry of Health. Fifty-eight people with stroke participated in the study. Groups 1 and 2 performed daily 600 repetitions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 58 publications
1
30
0
2
Order By: Relevance
“…A total of 16 studies were included in the study (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). The search of the databases and the reference list of the relevant studies yielded 1,023 hits in which 17 hits were provided from the reference list of the relevant studies.…”
Section: Results Study Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 16 studies were included in the study (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). The search of the databases and the reference list of the relevant studies yielded 1,023 hits in which 17 hits were provided from the reference list of the relevant studies.…”
Section: Results Study Selectionmentioning
confidence: 99%
“…The range for the sample size in the studies was between one and 58 participants. However, only four studies reported how the sample size was calculated (22)(23)(24)37). The studies were published between 2005 and 2021.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations